Legal Analysis of Silent Treatment Behavior and the Concept of Al-Hajr in Marital Relationships - Pratista, Farida; Tyas, Laksani Ciptaning; N, Rachmadini Ratna (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2025)
Silent treatment in marital relationships is rarely recognized as a violation of the law, but in fact this behaviour can be categorized as emotional abuse, if it is proven to cause severe psychological distress. This act is almost the same as the concept of al-Hajr in the perspective of Islamic law. This study aims to examine the impact and characteristics of silent treatment, as well as its relevance to the concept of al-Hajr in an Islamic law. The research method used was normative, with a descriptive comparative approach, which include data sources from laws, interpretation books, and other relevant literature. The results of the study confirm that the concepts of al-Hajr   and silent treatment in domestic relationships are very different, both in terms of definition, purpose and timing. In the context of nusyūz, al-Hajr is used as an educational measure with the aim of improvement. In contrast, silent treatment is generally carried out without reasons or objectives. Thus, this study clarify the misconception that Islam permits silent treatment, as it permits the concept of al-Hajr, which has a basis in Sharia law, while silent treatment is a form of injustice that is not taught in Islam.